Insights from the first Brazilian Symposium on Human Biometeorology - Krüger, Eduardo; Gomes, Ana Carla Dos Santos; Lucio, Paulo Sérgio; Gobo, João Paulo Assis; Nedel, Anderson Spohr; Gonçalves, Fabio Luiz Teixeira; Piacenti-Silva, Marina [UNESP]; Di Napoli, Claudia; Lam, Cho Kwong Charlie (Zeppelini Editorial e Comunicacao, 2023)
A current systematic literature review has stated several deficiencies and knowledge gaps in biometeorology research conducted in Brazil. This finding encouraged a group of local professionals in the field to foster research initiatives in topics and regions yet unexplored in the country. Motivated by that, the group organized the first Brazilian Symposium on Human Biometeorology between July 4 and 8, 2022, in Natal (RN), northeastern Brazil. This paper aims to summarize the main studies presented at the symposium and highlight a few ideas that could be pursued next in human biometeorology in future research initiatives.
Reflexões sobre o primeiro Simpósio Brasileiro de Biometeorologia Humana
Keywords: climate-driven diseases; heat-related mortality; urban climatology